2019
DOI: 10.1073/pnas.1900890116
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the complexes of oxidative phosphorylation triggers the remodeling of cardiolipin

Abstract: Cardiolipin (CL) is a mitochondrial phospholipid with a very specific and functionally important fatty acid composition, generated by tafazzin. However, in vitro tafazzin catalyzes a promiscuous acyl exchange that acquires specificity only in response to perturbations of the physical state of lipids. To identify the process that imposes acyl specificity onto CL remodeling in vivo, we analyzed a series of deletions and knockdowns in Saccharomyces cerevisiae and Drosophila melanogaster, including carriers, membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 57 publications
6
74
0
Order By: Relevance
“…5A), probably due to the majority of mitochondrial remodeling occurring already during the diauxic shift. Due to its conical shape, CL is known to be abundant in areas of high membrane curvature; moreover, this lipid has been implicated in the stabilization of individual complexes of the respiratory chain (39). We found that as cells shift toward respiration, the acyl-chain composition of the CL species also moves toward a higher degree of unsaturation ( Fig.…”
Section: Stoichiometric Evaluation Of Atp Synthase Subunits and Remodmentioning
confidence: 69%
See 1 more Smart Citation
“…5A), probably due to the majority of mitochondrial remodeling occurring already during the diauxic shift. Due to its conical shape, CL is known to be abundant in areas of high membrane curvature; moreover, this lipid has been implicated in the stabilization of individual complexes of the respiratory chain (39). We found that as cells shift toward respiration, the acyl-chain composition of the CL species also moves toward a higher degree of unsaturation ( Fig.…”
Section: Stoichiometric Evaluation Of Atp Synthase Subunits and Remodmentioning
confidence: 69%
“…5 C and D). It has previously been speculated that the increase in CL unsaturation enables an increase in membrane fluidity, in turn allowing cristae to increase in curvature and accommodate more ATP synthase for respiration (39). This observation toward CL reconfiguration was further supported by the proteomic data, which showed an up-regulation of the Mitochondrial CL-specific phospholipase Cld1; the Mitochondrial phosphatidylglycerolphosphatase (PGP phosphatase) Gep4; the Phosphatidylglycerolphosphate synthase Pgs1, a rate-limiting step in the synthesis of CL; the Mitochondrial phosphatidate cytidylyltransferase (CDP-DAG synthase) Tam41, also required for CL biosynthesis; and the Lysophosphatidylcholine acyltransferase Taz1, involved in the CL acyl-chain remodeling (Fig.…”
Section: Stoichiometric Evaluation Of Atp Synthase Subunits and Remodmentioning
confidence: 99%
“…Pointing to the importance of membrane morphology for cardiolipin biogenesis, a recent study found that cardiolipin levels are strongly reduced in cells lacking both proposed pathways for cristae formation, the Mgm1‐dependent pathway and the MICOS/phospholipid import‐dependent pathway (see section ‘Inner membrane dynamics’) . Similarly, cardiolipin remodelling and stability are severely affected in mutants with global defects of the respiratory chain, indicating that morphology and/or the high protein:lipid ratio of the inner membrane is required for cardiolipin metabolism .…”
Section: Nonbilayer‐forming Phospholipidsmentioning
confidence: 99%
“…In addition, the yeast inner membrane protein Mdm33 may enable inner membrane fission by regulating phospholipid homoeostasis and compartmentalization, possibly together with the prohibitins that are amongst Mdm33's interaction partners . Thus, phospholipid synthesis and remodelling may take place in specialized membrane subdomains that are maintained by membrane shaping or scaffolding proteins .…”
Section: Nonbilayer‐forming Phospholipidsmentioning
confidence: 99%
“…CL plays a central role in many mitochondrial processes, including apoptosis, mitophagy, signaling, fission/fusion dynamics, and energy metabolism (14,15). Within the protein-rich MIM, CL mediates many interactions with peripheral and integral membrane proteins (16,17), underpinning its role in the assembly of OXPHOS complexes into supercomplexes (18,19).…”
mentioning
confidence: 99%